Service Quality and LMS Usage in University: The Mediation Role of User Satisfaction and the Moderating Role of Flexibility-Oriented Culture - Tri Wahyudi; Anang Kistyanto; Andre Dwijanto Witjaksono; Joshi Maharani Wibowo (Universitas Negeri Surabaya, 2026)
Objective: This research seeks to analyse the impact of service quality and user satisfaction on system use directly, as well as through the moderating effect of flexibility-oriented culture and system use as a mediator in the context of the SiDia LMS at Universitas Negeri Surabaya (Unesa). Method: An explanatory quantitative approach with data analysis using PLS SEM assisted by SmartPLS 4.0 software was used in this study. The research sample consisted of active lecturers at Unesa, selected using proportional stratified random sampling, resulting in 264 respondents. Results: The findings show that service quality has a significant effect on user satisfaction but does not have a significant effect on system use in the use of SiDia LMS at Unesa. User satisfaction is confirmed to have a significant effect on system use and fully mediates the association between service quality and system use. A flexibility-oriented culture failed to act as a moderating variable. The accomplishment of SiDia implementation at Unesa is more determined by the quality of user experience and system support services than by organisational flexibility culture. SiDia development needs to focus on improving the quality of operational services and integrating LMS usage through user experience analytics and differentiated support. Novelty: This research focuses on developing a model for LMS success by integrating mediation and moderation mechanisms simultaneously within the ISSM framework, incorporating a flexibility-oriented culture as an organisational contextual factor, which is still rarely done.